2021
DOI: 10.1002/ajb2.1763
|View full text |Cite
|
Sign up to set email alerts
|

Loss of branches due to winter storms could favor deciduousness in oaks

Abstract: Premise Ecologists have an incomplete understanding of the factors that select for deciduous, evergreen, and marcescent leaf habits. Evergreens have more opportunities for photosynthesis but may experience costs when abiotic conditions are unfavorable such as during ice and windstorms. Methods We documented branch loss for species of oaks (Quercus spp.) in a common garden in California during an unusual windstorm. Results Branches of marcescent trees were more likely to break during the storm, and this pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…A null hypothesis for any trait, including marcescence, is that it is an evolutionary byproduct with no current adaptive function. There is a strong phylogenetic pattern at our site for leaf marcescence, with nearly all species exhibiting the trait belonging to the plant order Fagales (oaks, beech, and chestnut; Appendix S1: Figure S4), a conclusion that has been noted elsewhere (Karban & Pearse, 2021). In these plant families, it is possible that the marcescent leaf habit may be a byproduct of incomplete evolution of deciduousness from evergreen ancestors.…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…A null hypothesis for any trait, including marcescence, is that it is an evolutionary byproduct with no current adaptive function. There is a strong phylogenetic pattern at our site for leaf marcescence, with nearly all species exhibiting the trait belonging to the plant order Fagales (oaks, beech, and chestnut; Appendix S1: Figure S4), a conclusion that has been noted elsewhere (Karban & Pearse, 2021). In these plant families, it is possible that the marcescent leaf habit may be a byproduct of incomplete evolution of deciduousness from evergreen ancestors.…”
Section: Figuresupporting
confidence: 76%
“…By extension, delayed autumn senescence might increase marcescence, or early autumn frosts might lead to failure to form a proper abscission layer. A recent study of California oaks demonstrated that marcescent species are at higher risk to branch loss during winter storms than other species (Karban & Pearse, 2021). Longer term observational data are needed, alongside marcescent leaf removal experiments.…”
mentioning
confidence: 99%